Synthetic Circular RNA Functions as a miR-21 Sponge to Suppress Gastric Carcinoma Cell Proliferation - Xi Liu; John M. Abraham; Yulan Cheng; Zhixiong Wang; Zhe Wang; Guanjun Zhang; Hassan Ashktorab; Duane T. Smoot; Robert N. Cole; Tatiana N. Boronina; Lauren R. DeVine; C. Conover Talbot, Jr.; et al. (Molecular Therapy: Nucleic Acids, 2018)
MicroRNA (miR) sponges containing miR binding sequences constitute a potentially powerful molecular therapeutic strategy. Recently, naturally occurring circular RNAs (circRNAs) were shown to function as efficient miR sponges in cancer cells. We hypothesized that synthetic circRNA sponges could achieve therapeutic loss-of-function targeted against specific miRs. Linear RNA molecules containing miR-21 binding sites were transcribed in vitro; after dephosphorylation and phosphorylation, circularization was achieved using 5′-3′ end-ligation by T4 RNA ligase 1. circRNA stability was assessed using RNase R and fetal bovine serum. Competitive inhibition of miR-21 activity by a synthetic circRNA sponge was assessed using luciferase reporter, cell proliferation, and cell apoptosis assays in three gastric cancer cell lines. circRNA effects on downstream proteins were also delineated by Tandem Mass Tag (TMT) labeling (data available via ProteomeXchange identifier PRIDE: PXD008584), followed by western blotting. We conclude that artificial circRNA sponges resistant to nuclease digestion can be synthesized using simple enzymatic ligation steps. These sponges inhibit cancer cell proliferation and suppress the activity of miR-21 on downstream protein targets, including the cancer protein DAXX. In summary, synthetic circRNA sponges represent a simple, effective, convenient strategy for achieving targeted loss of miR function in vitro, with potential future therapeutic application in human patients. Keywords: synthetic circular RNA, microRNA sponge, microRNA loss-of-function, gastric carcinoma, molecular therapy